Earnings management and audit report lag: The role of audit risk-Tunisian evidence - Imen Fakhfakh; Anis Jarboui (Contabilitate şi Informatică de Gestiune, 2022)
Research question: This study investigates and analyzes the influence of earnings management on audit report lag. It also intends to develop a thorough understanding regarding the mediating effect of audit risk on this relation. Motivation: The outcomes of this paper will help to bridge the knowledge gap related to this issue in developing countries due to the importance of audit delay as it relates to corporate transparency. Idea: The issue of reporting delay is important as it relates to corporate transparency. Data: This study is based on a sample consisting of 28 Tunisian companies listed in the Tunis Stock Exchange (TSE) over the periods 2005 to 2010 (pre-2011 revolution) and 2011 to 2017 (post-2011 revolution). Tools: Consisting of 364 observations for the whole period, Structural Equation Modeling (SEM) approach is applied and three models are developed to examine the direct and the indirect link between earnings management and audit report lag. Findings: The results show that firms which manage their earnings upward are more likely to accelerate the release of their financial statements. In addition, in the Tunisian context, audit risk mediates the relationship between earnings management and audit report lag. Contribution: This study extends the existing literature by examining the mediation effect of audit risk on the relationship between earnings management and audit report lag.